Asiantuntijuus ja ammatillinen osaaminen päiväkodin toimintakulttuurissa - Johansson, Päivi (fi=Turun yliopisto|en=University of Turku|, 2017)
The study determines how expertise and professional competence is taken into consideration and explained in the operational culture of a day-care center. The questionnaire maps out how the operational concept, plans and objectives are described as a basis of operation. The focus lies on the dialogue, decision-making, planning and evaluation processes. Day-care centers operate on teamwork basis, and thus the study will also map out the distribution of work and responsibilities. In this study, expertise is considered to be a social, interactive process between the individual and the environment. This is a qualitative cultural study. The open questions on the questionnaire help in the classification, description and conceptualization of answers with the help of the concepts of expertise, professional competence and operational culture employed in this study. A phenomenological-hermeneutical approach in employed, taking the preconceptions of the researcher into account when interpreting the answers. The aim of the study is to turn ‘the widely known’ into facts and to shed light on the different definitions of work. The sampling of the study, 118, consisted of 62.1% of the studied municipality’s early childhood education personnel in 2009. 29 of them replied to the survey. The response rate was 24.6%. Ideally, operational concepts and their practical implementation support expertise and professionalism in day-care centers. The operational concepts go hand in hand with the objectives of work, which are defined based on the growth and development of children and the needs of families. The aim of meeting practices is to support expertise and professionalism. The distribution of work and responsibilities does not support the expertise and professionalism of employees. Work is mostly performed on an ‘everyone does everything’ basis and according to shifts. However, employees considered the modes of work and operation to be mostly unambiguous, as the employees had participated in the decision-making process. Evaluation is mainly targeted at the actions of work communities and teams, distribution of work, work environment and the wellbeing of personnel. Fewer responses mentioned the realization of goals, cooperation with parents, the growth and development of children and the operation of the child group.